2013
DOI: 10.1039/c3cp50932j
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of noble-gas hydrides by a water environment: calculations for HXeOH@(H2O)n, HXeOXeH@(H2O)n, HXeBr@(H2O)n, HXeCCH@(H2O)n

Abstract: HNgY molecules are chemically-bound compounds of a noble-gas atom (Ng) with a hydrogen and with an electronegative group Y. There is considerable current interest in the stability of these species in different types of media. The kinetic stability of several compounds, HXeOH, HXeOXeH, HXeBr and HXeCCH, in water clusters is explored by ab initio calculations. It is found that the kinetic stability of the compounds is reduced by the water environment, generally falling off with the number of H 2 O molecules. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The water molecule hydrogens are slightly tilted out from the plane of the hydrogen bond in analogy to water dimer equilibrium structure. Both structures are in accordance with previous studies on the HXeOH-H2O complex [25][26][27]29,39]. However, discrepancy exists between the current study and previous computational study.…”
Section: Hxeoh/sh Complexes With H2osupporting
confidence: 88%
See 2 more Smart Citations
“…The water molecule hydrogens are slightly tilted out from the plane of the hydrogen bond in analogy to water dimer equilibrium structure. Both structures are in accordance with previous studies on the HXeOH-H2O complex [25][26][27]29,39]. However, discrepancy exists between the current study and previous computational study.…”
Section: Hxeoh/sh Complexes With H2osupporting
confidence: 88%
“…These studies characterized the 1:1 hydrogen-bonded complex thoroughly, and indicated moderate hydrogen bond between the complex subunits. The computational investigations by Nemukhin et al [25] also demonstrated that hydrogen-bonded cluster involving more than one water molecule decrease the stability of HXeOH, a property that seems to be common for all the noble-gas containing molecules in the presence of increasing number of water molecules [29]. Up-to-date, there appear to be no studies on HXeOH-H 2 S, HXeSH-H 2 O or HXeSH-H 2 S, which could shed light on the similarities and differences of the oxygenand sulfur-containing complexes and their properties to aid possible future experimental endeavors to prepare and identify such complexes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Any species can react or interact with an inert molecule and can destabilize the whole complex, as observed for the HXeOH-water complex. 15,21 In contrast to water complexes of HXeOH, HXeCCH and HKrCCH have been found to be stable in the acetylene clusters. 22,23 Water is the most ubiquitous solvent in nature and plays an important role in the atmosphere as well as in many chemical reactions.…”
Section: Introductionmentioning
confidence: 98%
“…Although just limited noble gas molecules have been synthesized experimentally, many types of noble gas compounds are possible from theoretical point of view . This list includes compounds which have been also observed experimentally; such as XeF 6 , KrF 2 , HArF, clathrates and clathrate hydrates, coordination compounds, hydrates (Xe.6H 2 O), HeH + , oxyfluorides (XeOF 2 , XeOF 4 , Xe 2 O 3 F 2 , XeO 2 F 4 ), and fullerene compounds.…”
Section: Introductionmentioning
confidence: 99%